The onset of energetic particle irradiation in Class 0 protostars - Favre, C.; López-Sepulcre, A.; Ceccarelli, C.; Dominik, C.; Caselli, P.; Caux, E.; Fuente, A.; Kama, M.; Le Bourlot, J.; Lefloch, B.; Lis, D.; Montmerle, T.; et al. (Astronomy and astrophysics (Berlin), 2017)
Context. The early stages of low-mass star formation are likely to be subject to intense ionization by protostellar energetic MeV particles. As a result, the surrounding gas is enriched in molecular ions, such as HCO+ and N2H+. Nonetheless, this phenomenon remains poorly understood for Class 0 objects. Recently, based on Herschel observations taken as part of the key programme Chemical HErschel Surveys of Star forming regions (CHESS), a very low HCO+/N2H+ abundance ratio of about three to four, has been reported towards the protocluster OMC-2 FIR4. This finding suggests a cosmic-ray ionization rate in excess of 10-14 s-1, much higher than the canonical value of ζ = 3 × 10-17 s-1 (value expected in quiescent dense clouds). Aims. We aim to assess the specificity of OMC-2 FIR4, we have extended this study to a sample of sources in low- and intermediate mass. More specifically, we seek to measure the HCO+/N2H+ abundance ratio from high energy lines (J ≥ 6) towards this source sample in order to infer the flux of energetic particles in the warm and dense gas surrounding the protostars. Methods. We have used observations performed with the Heterodyne Instrument for the Far-Infrared spectrometer on board the Herschel Space Observatory towards a sample of nine protostars. Results. We report HCO+/N2H+ abundance ratios in the range of five up to 73 towards our source sample. The large error bars do not allow us to conclude whether OMC-2 FIR4 is a peculiar source. Nonetheless, an important result is that the measured HCO+/N2H+ ratio does not vary with the source luminosity. At the present time, OMC-2 FIR4 remains the only source where a high flux of energetic particles is clearly evident. More sensitive and higher angular resolution observations are required to further investigate this process.